2004
DOI: 10.1152/ajpheart.01235.2003
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial endothelium in the avascular frog heart: role for diffusion of NO in control of cardiac O2 consumption

Abstract: .-We investigated the role of nitric oxide (NO) in the control of myocardial O 2 consumption in the hearts of female Xenopus frogs, which lack a coronary vascular endothelium and in which the endocardial endothelium is the only source of NO to regulate cardiac myocyte function. Hence, frogs are an ideal model in which to explore the role of diffusion of NO from the endocardial endothelium (EE) without vascular endothelial or cardiac cell NO production. In Xenopus hearts we examined the regulation of cardiac O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition, we determined that A. niger catalase (10 Ϫ5 mol/l) and ethanol (10 Ϫ7 mol/l) prevented NO release in the endocardial endothelial preparation, since A. niger catalase would metabolize any H 2O2 produced by Lzm-S, whereas ethanol would prevent the formation of compound I. Finally, it was also confirmed that the electrode signal measured NO release by placing another agonist, bradykinin (10 Ϫ5 mol/l), into the endocardial preparation (1). NO signals were determined with bradykinin alone, bradykinin with L-NMMA pretreatment (10 Ϫ4 mol/l), L-NMMA pretreatment alone, and bradykinin with D-NMMA pretreatment (10 Ϫ4 mol/l).…”
Section: Real-time Measurements Of Endocardial Endothelial No Formatimentioning
confidence: 74%
“…In addition, we determined that A. niger catalase (10 Ϫ5 mol/l) and ethanol (10 Ϫ7 mol/l) prevented NO release in the endocardial endothelial preparation, since A. niger catalase would metabolize any H 2O2 produced by Lzm-S, whereas ethanol would prevent the formation of compound I. Finally, it was also confirmed that the electrode signal measured NO release by placing another agonist, bradykinin (10 Ϫ5 mol/l), into the endocardial preparation (1). NO signals were determined with bradykinin alone, bradykinin with L-NMMA pretreatment (10 Ϫ4 mol/l), L-NMMA pretreatment alone, and bradykinin with D-NMMA pretreatment (10 Ϫ4 mol/l).…”
Section: Real-time Measurements Of Endocardial Endothelial No Formatimentioning
confidence: 74%
“…NO produced by Ca 2+ -dependent NOS in endothelium, in cardiomyocytes and in cardiac nerves serves a number of important roles in the regulation of cardiac function including coronary vasodilation, inhibiting platelet and neutrophil actions, antioxidant effects, modulation of cardiac contractile function, and inhibiting cardiac oxygen consumption [ 3,7,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. In excess concentrations, NO could be potentially toxic.…”
Section: Evidence For Increased Nitrosative Stress In Heart Failurementioning
confidence: 99%
“…The role of telocytes network is still speculative: heterocellular signalling, cardiac renewing, immune surveillance and/or mechanotransduction [11, 12, 19]. We cannot overlook the fact that endocardium is, at least conceptually, something like blood–brain barrier, mainly a ‘blood–heart barrier’ or a ‘blood–myocardium barrier’[29]. Apparently, telocytes, which seem to be the main population in the sub‐epithelial layer of endocardium, might have a role in this ‘blood–myocardium barrier’.…”
mentioning
confidence: 99%